Streptococcus A Rapid Diagnostic Testing in England Community Pharmacies: Clinical and Economic Impact of Empowering Pharmacists in Management of Sore Throat - Kay Edokpayi; Patricia Aluko; Flora Ka Kei Cheng; Darush Attar-Zadeh; Anne Dawson (Journal of Primary Care & Community Health)
Introduction: Many patients with sore throat receive antibiotics from their general practitioners (GPs); however, only a minority are affected by bacterial infection, often streptococcal A (Strep A). Rapid diagnostic test can improve diagnosis, guide treatment decisions and direct patients when required for appropriate self-care. This study investigates the potential benefit of Strep A rapid tests in pharmacies for sore throat patients, with the aim of maximising healthcare resources. Methods: Participants over 16 years old were screened using FeverPAIN scores, and those with high scores were tested for Strep A. To estimate avoided GP visits, participants completed a questionnaire on treatment choice (Accident & Emergency (A&E) GP visit, pharmacist, self-care) if the diagnostic service was unavailable. Results and Conclusion: Majority (86%) tested negative. The questionnaire revealed that 67% could avoid GP visits. When extrapolated to the UK, this could result in an estimated annual saving of £263 million for the National Health Service (NHS) Despite not being recommended for routine use by NICE, the study suggests that such rapid diagnostic testing for Strep A, combined with FeverPAIN screening, could prevent antimicrobial misuse, alleviate NHS pressure and empower pharmacists. This is particularly relevant considering the recent implementation of the pharmacy-first service.